Implementation of a system-activity approach in the teaching of mathematics in the conditions of transition to GEF LLC - Aiupova L. B. (Educational environment today: development strategy, 2019)
The article "Implementation of the system-activity approach in teaching mathematics in the conditions of transition to the Federal State Educational Standards LLC" reveals the features of the system-activity approach and ways to implement it in line with the use of technology for the development of critical thinking. The focus is on methodological techniques: cluster, insert, sinwain, etc.
Keywords: системно-деятельностный подход; ФГОС; критическое мышление; обучение математике; system-activity approach; the federal state educational standard; the process of teaching mathematics; the technology of developing critical thinking